Equitable and effective climate policy: Integrating less developed countries into a global climate agreement - Lucas Bretschger; Alexandra Vinogradova (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
The paper derives general rules for equitable burden sharing in international climate policy. The focus is on a new social climate contract between developed and less developed countries (LDCs) which preserves competitiveness of the former and the ”right to development” of the latter. We formally derive conditions under which an LDC keeps the ”right to development” but voluntarily agrees to participate in stringent international climate policy. Two types of policies are analyzed, one with a predefined transfer and the other with a transfer that is tied to emissions-control efforts. We show that offering only one or the other option is inefficient. Chances for a comprehensive agreement are higher when a menu of policy options is available. The number and diversity of LDCs willing to join a global climate treaty is higher when a variety of policy alternatives is available.
Keywords: Q43; O47; Q56; O41; 330; Climate policy; less developed countries; equitable burden sharing; right to development; international climate agreement